Excellent Response to Atezolizumab After Clinically Defined Hyperprogression Upon Previous Treatment With Pembrolizumab in Metastatic Triple-Negative Breast Cancer: A Case Report and Review of the Literature - Feng, Dongfeng; Guan, Yaping; Liu, Mingguo; He, Shuqian; Zhao, Weipeng; Yin, Beibei; Liang, Jing; Li, Yan; Wang, Jun (Frontiers in Immunology, 2021)
Immunotherapy with immune checkpoint inhibitors (ICIs), including programmed cell death protein-1 (PD-1) and programmed cell death ligand-1 (PD-L1) inhibitors, has revolutionized the systematic treatment of advanced and metastatic solid tumors. However, the response rate to ICIs is unsatisfactory, and unexpected hyperprogressive disease (HPD) is even observed in a small subgroup of patients. Patients with HPD usually have worsening clinical symptoms and poorer survival, and therapeutic strategies are extremely limited. Here, we presented a patient with HPD who had used a PD-L1 inhibitor and was highly responsive to the sequential use of a PD-L1 inhibitor. A 67-year-old woman with metastatic triple-negative breast cancer was treated with pembrolizumab plus chemotherapy after progression on previous multiple-line chemotherapy treatments. After 2 cycles of treatments, she rapidly developed HPD, as confirmed by radiological evaluation and worsening symptoms. At that time, pembrolizumab was discontinued, and she switched to the PD-L1 inhibitor atezolizumab plus chemotherapy. This patient partially responded to atezolizumab plus chemotherapy without experiencing severe drug-related adverse effects. This is the first reported case of metastatic breast cancer in a patient with radiologically confirmed HPD after pembrolizumab therapy in which successful rechallenge with atezolizumab relieved clinical symptoms. Further studies with larger sample sizes involving a deeper translational investigation of HPD are needed to confirm the efficacy and mechanism of sequential application of different ICIs for the clinical management of HPD.